In vitro assembly of infectious nucleocapsids of bacteriophage phi 6: formation of a recombinant double-stranded RNA virus. - Olkkonen, V M (1990)
A system is described for assembling infectious bacteriophage phi 6 nucleocapsids in vitro. Procapsids encoded by cDNA copies of genomic segment L in Escherichia coli were used to package and replicate viral RNA segments. The resulting filled particles were shown to be capable of infecting host cell spheroplasts after incubation with purified nucleocapsid shell protein P8. The infected spheroplasts yielded infectious virions. A modified cDNA-derived RNA segment was inserted into virions by this method. The resulting infectious virions contained the same 4-base-pair deletion as the modified cDNA. These findings support the contention that the preformed procapsids are the "machine" that replicates the phi 6 genome, by showing that the cDNA-derived procapsids are competent to package and replicate RNA properly.